A history of the french suburbs - de Wenden, Catherine Wihtol (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
Beyond its present form made up of violence and desperation, the explosion of the suburbs which took place a year ago in november 2005 is revealing of deeper issues which have their root in the french he sitations between a policy of labour immigration and a policy of settlement: housing policy after the reabsorption of the shanty towns, consequences of the closure on employee immigration and on family reunion, ascent of Islam, institutional discriminations, weak geographical mobility,construction of with drawing identities, anger... The article analyzes thirty years of integration policy in the suburbs from observations, research in the field and personal analysis, putting the accent on the fact that the young are not asking for comunitarism but are demanding that the republican principles they were taught also be applied to them. The issue of police violence is at the heart of this debate.